MiR-669b-5p inhibits the Alzheimer's disease development via regulation of CHEK2 in Neuro2a APPSwe/Δ9 cells: MiR-669b-5p inhibits the Alzheimer's development - A, Mula; Bai, Yan; Hu, Bingcheng; Su, Yunhai; Yuan, Xingxing (Cellular and Molecular Biology, 2023)
DNA damage of neurons is accumulated in Alzheimer's disease (AD). DNA damage-activated Checkpoint kinase 2 (CHEK2) is evaluated in Aβ-treated Neuro2a APPSwe/Δ9 cells, and the miR-669b-5p was specifically down-regulated. However, the underlying molecular mechanism between CHEK2 and miR-669b-5p in Neuro2a APPSwe/Δ9 cells remains unclear. This research discovers that in A-treated Neuro2a APPSwe/Δ9 cells, CHEK2 expression and miR-669b-5p expression were inversely correlated. In addition, miR-669b-5p mimics increased cell survival and proliferation in Neuro2a APPSwe/Δ9 cells while decreasing the production of inflammatory cytokines and cell death. Furthermore, it is observed that CHEK2 was a miR-669b-5p downstream target gene and that CHEK2 restored the miR-669b-5p's functions. According to this research, miR-669b-5p is a potential therapy for Alzheimer's patients since it slows the advancement of the disease.